Progress on built environment and cardiovascular health - Juexin SHI; Feng LU; Bixiong YE; Shaoxia DONG (环境与职业医学, 2023)
The construction of healthy cities is an important part of the construction of a healthy China and the Healthy China Initiative, and a good built environment helps improve the health governance capacity of a city and the health level of the population. With the development of urbanization, the acceleration of global aging, and the improvement of people's living standards, cardiovascular diseases have gradually become a primary threat to human health. In this paper, we introduced the effects of built environment on cardiovascular diseases such as hypertension, atherosclerosis, and diabetes in detail. At the same time, based on two hypotheses of built environment on cardiovascular health, we summarized the roles of behavioral patterns andenvironmental factors in the relationship between built environment and cardiovascular health. We proposed that behavioral patterns and environmental factors may play important mediating roles in the relationship between built environment and cardiovascular health, which can aid to better quantify the exposure-response relationship between built environment and cardiovascular health and provide a scientific basis for constructing a harmonious and healthy city.